Optimalisasi Peran Pejabat Pembuat Akta Tanah dalam Mitigasi Risiko Pencucian Uang Pada Transaksi Properti - Pranoto, Velicia Marveline; Amidjoyo, Andreas Audy Tjokro; Christianto, Hwian (Magister Kenotariatan Universitas Surabaya, 2026)
Indonesia’s positive economic growth until 2025 has been accompanied by increasingly complex and adaptive patterns of money laundering, particularly through the land and property sector. Property transactions are considered vulnerable to concealing illicit funds, prompting the state to position Land Deed Officials (PPAT) as reporting parties and gatekeepers through the obligation to implement the Principle of Recognizing Service Users (PMPJ). This study analyzes PMPJ implementation by PPAT in preventing money laundering from the perspective of responsive legal theory and examines Indonesia’s legal policy in shaping the role of PPAT within the anti–money laundering system. The findings indicate that PMPJ implementation by PPAT has not been substantively effective, as it tends to be formalistic and administratively oriented rather than risk based. The transaction threshold of Rp 100.000.000,- is no longer relevant to current property market realities, resulting in the loss of PMPJ’s selective preventive function. However, the regulatory approach remains largely top-down and insufficiently adapted to the empirical characteristics of land transactions. Therefore, more responsive, proportional, and fair legal reform is required to enhance the effectiveness of money laundering prevention in the land and property sector.